Accuracy of Flash Glucose Monitoring in a Patient with Dravet Syndrome on a Ketogenic Diet - Kortas, Aline; Schiller, Katharina; Unterholzner, Gabriele; Rauchenzauner, Markus (Neuropediatrics, 2020)
We herein report the case of a 3-year-old girl with severe myoclonic epilepsy of infancy known as Dravet syndrome (DS) on a ketogenic diet (KD) whose glucose concentrations were controlled by using a flash glucose monitoring system. Two-hundred ninety-three events of moderate hypoglycemia with a minimum of 45 mg/dL, not related to day or night, were recorded during the observational period. Hypoglycemia rate declined from 24.5% of all measurements to 11.8% over time; one hypoglycemia-associated seizure and one seizure due to ketone concentrations below the therapeutic range were observed. In summary, this case report broadens our understanding of hypoglycemia risk in patients with DS on a KD. Especially in childhood, the painless and easy detection of low glucose concentrations might lead to improved cognitive performance, and the reduction of hypoglycemia-induced seizures.
Keywords: Dravet syndrome; ketogenic diet; flash glucose monitoring; children